THE LESSON OF IMPLEMENTING NON-DISCRIMINATION PRINCIPLE ON INDONESIA-US CLOVE CIGARETTES CASE - Johan, Eva (UI Scholars Hub, 2013)
The Indonesian government recently won for keeping its rights on Clove Cigarette Case in WTO. It became a winning diplomacy on Indonesia trade. Indonesia has an objection on United States cigarette policy, which prohibit product of clove cigarette (mostly imported by Indonesia) in United States, because such policy violate one of the most important principle on WTO, Non-Discrimination Principle, which are Most Favoured Nations (MFN) and National Treatment. Indonesia won this case in both, Panel and Appellate Body. This winning is not only important for Indonesia but for all country, mainly for Developing and Less Developing Country member of WTO. This paper will examine the significance and contents of Non Discrimination Principle from the perspective of Indonesia-United States Tobacco Case.